A tale of two policies: prudential regulation and monetary policy with fragile banks - Ignazio Angeloni; Ester Faia (Kiel Institute for the World Economy (IfW), 2009)
We introduce banks, modeled as in Diamond and Rajan (JoF 2000 or JPE 2001), into a standard DSGE model and use this framework to study the role of banks in the transmission of shocks, the effects of monetary policy when banks are exposed to runs, and the interplay between monetary policy and Basel-like capital ratios. In equilibrium, bank leverage depends positively on the uncertainty of projects and on the bank's relationship lender skills, and negatively on short term interest rates. A monetary restriction reduces leverage, while a productivity or asset price boom increases it. Procyclical capital ratios are destabilising; monetary policy can only partly offset this effect. The best policy combination includes mildly anticyclical capital ratios and a response of monetary policy to asset prices or leverage.
Keywords: 330; Capital requirements; leverage; bank runs; combination policy; market liquidity; Bankenkrise; Bankenliquidität; Bankenaufsicht; Basel II; Eigenkapitalvorschriften; Kapitalstruktur; Geldpolitik; Schock; Transmissionsmechanismus; Theorie